Genetic polymorphism in amphibian populations of Protected Areas in the south of Western Siberia and the Urals - Zhigileva, Oksana N.; Artishevskaya, Viktoria S.; Burakova, Anna V.; Baitimirova, Ekaterina A. (Nature Conservation Research: Заповедная наука, 2018)
Amphibians are an important but vulnerable component of biodiversity. Climatic changes and anthropogenic transformation of the environment can lead to changes in spawning times and habitat boundaries, causing adverse genetic processes in populations. In the present study, we assess genetic variation and differentiation among 184 individuals of four amphibian species (Rana arvalis, Rana amurensis, Rana temporaria, Bufo bufo) from seven localities of the south of Western Siberia and the Urals, Russia. To investigate the genetic diversity of these species, we used six primers for inter simple sequences repeat (ISSR) markers. Nei's gene diversity (h) varied from 0.169 to 0.311 in the local populations of amphibians; the diversity was the smallest in the common toad B. bufo and the highest in the Siberian wood frog R. amurensis. Populations of B. bufo and the moor frog R. arvalis were highly differentiated (mean multilocus GST = 0.249 and 0.268, respectively). Nei's original measures of genetic identity (I) and genetic distance (D) among the toad populations were comparable with these indexes among the studied brown frog populations. These results indicate that B. bufo and R. arvalis have a well-defined population structure with restricted gene flow between populations. We also identified a high level of genetic diversity among eggs of R. arvalis not observed in adults. Our results provide genetic evidence that all the studied species have high adaptive potential and genetic structure typical for amphibian populations. The presented data are intended to fill the gap in studying the genetic structure of the amphibian populations of the south of Western Siberia and the Urals. The data on different levels of genetic variability in amphibian populations from protected areas show their different value for conservation management. The presence of genetically impoverished populations requires monitoring of genetic diversity of amphibians. These data will be useful for conservation concerns, especially for developing appropriate management strategies.